INFORMAL STATISTICAL REASONING OF STUDENTS TAKEN FORMAL STATISTICS LEARNING RELATED TO DISTRIBUTION - Rufiana, Intan Sari; Sa'dijah, Cholis; Subanji, Subanji; Susanto, Hery; As'ari, Abdur Rahman (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
This research aims at describing students? statistical reasoning in graphics statistics representation related to distribution. The subjects of this research were students of semester IV of Program of Study Mathematics Education of Muhammadiyah University Ponorogo who have taken a basic statistics course. These subjects were chosen because they have taken a course related to descriptive statistics which discusses graphics representation and data distribution. The data collection technique used essay test related to graphics representation. In addition, an interview was also conducted to confirm students? answer. This research finding shows that statistical reasoning of semester IV students of Mathematics Education whose statistics ability is poor belong to pre-structural level and whose statistics ability is high belong to multi-structural and relational level. The high skilled students could conclude the data with statistical reason even though they used informal terms. Students with multi-structural and relational level regard that variety is a standard showing the numbers of different data among others, not on the different value from the average. Students with relational reasoning level were able to generate graphics concluding by connecting the central tendency and distribution scale.